Clinical value and limitations of the preoperative C‐reactive‐protein‐to‐albumin ratio in predicting post‐operative morbidity and mortality after deceased‐donor liver transplantation: a retrospective single‐centre study. (4th July 2021) - Amygdalos, Iakovos; Bednarsch, Jan; Meister, Franziska Alexandra; Erren, David; Mantas, Anna; Strnad, Pavel; Lang, Sven Arke; Ulmer, Tom Florian; Boecker, Joerg; Liu, Wenjia; Jiang, Decan; Bruners, Philipp; et al.
Summary: Liver transplantation is still associated with a high risk of severe complications and post‐operative mortality. This study examines the predictive value of the preoperative C‐reactive‐protein‐to‐albumin ratio (CAR) regarding perioperative morbidity and mortality in deceased‐donor liver transplantation (DDLT) recipients. In total, 390 DDLT recipients between 05/2010 and 03/2020 were eligible. Predictive abilities of CAR were examined through receiver operating characteristic curve (ROC) analyses. Groups were compared using parametric and non‐parametric tests as appropriate. Independent risk factors for morbidity and mortality were identified using uni‐ and multivariable logistic regression analyses. A good predictive ability for CAR was shown regarding perioperative morbidity (comprehensive complication index ≥75, Clavien–Dindo score ≥4a) and 12‐month mortality, with an ideal cut‐off of CAR = 26%. Patients with CAR>26% had significantly higher median CCI scores (60 vs. 43, P < 0.001), longer intensive care unit (ICU, 5 vs. 4 days, P < 0.001) and hospital (28 vs. 21 days, P < 0.001) stays and higher 12‐month mortality rates (20% vs 6%, P < 0.001). Multivariable analyses identified CAR>26%, pre‐OLT inpatient hospitalization (including ICU) and post‐operative red blood cell transfusions as independent predictors of severe cumulative morbidity (CCI≥75). Preoperative CAR might be a reliable additional tool to predict perioperative morbidity and mortality in DDLT recipients. Abstract : The preoperative C‐reactive‐protein‐to‐albumin ratio is a valuable additional tool in predicting postoperative morbidity and mortality after deceased‐donor liver transplantation.